PENGELOLAAN ASET TANAH MILIK PEMERINTAH KOTA PEKANBARU DI KELURAHAN PULAU KARAM KECAMATAN SUKAJADI TAHUN 2012 - Wahyuni, Oci Dian; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study tried to find out how asset management Pekanbaru City Government-owned land in the Village of Karam Island District of the Year 2012 and actor Sukajadi inhibitors in the management of government-owned land assets Pekanbaru City Island in the Village of Karam District of Sukajadi 2012. The research is a descriptive qualitative research method. In the data collection researchers used observation, interview and documentation. By using key informants as a source of information about the study.From the findings of the data obtained Asset Management Pekanbaru City Owned Land in the Village of Karam Island District of Sukajadi of 2012 consisted of an inventory of land assets that include team building inventory, the initial data collection, check fidik and matching initial data. In lagalitas audit still found land not yet have the status of land titles, and an assessment of the assets that still need human resources with expertise in the assessment of the land assets, as well as optimalsiasi from the use of the asset is less clear, especially to land or buildings former Golkar building.Inhibiting factors not optimal Land Asset Management at Island Village of Karam District of Sukajadi caused by several factors that affect the human resource that is not working optimally, inadequate infrastructure, non-performance of an inventory of assets on a regular basis, the budget is not too big, and the constraints of non another technical.Keywords: Land Asset Management, Inventory, Legal Audit, Assessment, Optimizing Utilizatio